P0047PREVALENCE OF FABRY DISEASE IN DIALYSIS PATIENTS IN FRANCE (FABRYDIAL STUDY). (6th June 2020) - Sens, Florence; Guittard, Laure; Knebelmann, Bertrand; Moranne, Olivier; Choukroun, Gabriel; De-Précigout, Valérie; Couchoud, Cécile; Bravant, Estelle; Chakir, Mohammed A; Lancelot, Léa; Germain, Dominique P; Juillard, Laurent
Abstract: Background and Aims: Fabry Disease (FD) is an X linked lysosomal storage disease due to pathogenic α-galactosidase A (GLA) variants. It leads to damage in kidney and other organs. Numerous prevalence studies have been conducted over the past twenty years in ESRD patients in different countries. However, many screening studies did not perform confirmatory GLA variant analyses, and included recently recognized 'benign/likely-benign' variants, thereby inflating prevalence estimates. Thus, the prevalence of Fabry disease in patients with end-stage renal disease remains controversial. The FABRYDIAL study aimed to measure the prevalence of Fabry disease in patients aged 18 to 75 years and treated by chronic dialysis, either hemodialysis or peritoneal dialysis. Method: The study was conducted in France in 5 geographic sectors (Aquitaine, Ile-de-France, Rhône-Alpes and Picardie regions, and the Gard department). One hundred and twenty-four dialysis centers participated in the study, which targeted patients undergoing chronic dialysis during the week of November 20, 2017. The exclusion criteria were the existence of a proven nephropathy unrelated to FD (polycystic kidney disease, type 1 diabetes or biopsy-proven IgA nephropathy, membranous glomerulonephritis or ANCA-associated vasculitis), the absence of health insurance coverage or guardianship or tutelage. α-galactosidase A in men, and both α-galactosidase A and lyso-GL3 in women, were measured on a drop of dried blood during the usual care of patients. GLA gene sequencing was performed in patients in whom one biological value was outside normal values. If a genetic variant was identified, a multidisciplinary Diagnosis Validation Committee (DVC) concluded, based on precise literature, clinical, biological and genetic data, as to the reality of Fabry disease. Results: Among the 6, 032 patients aged 18 to 75 years under chronic dialysis during the period considered, 714 were no longer treated in the participating centers when the research staff visited for eligibility assessment. 1, 121 had non-inclusion criteria, which in 89% of cases were a confirmed diagnosis of kidney disease (by renal biopsy or other means) making the existence of Fabry disease very unlikely. 4, 197 patients met the inclusion criteria, of which 3, 088 were included (1, 888 men and 1, 200 women). Valid biological analyzes were available for 2815 patients (1721 men and 1094 women), and a genetic test was indicated for 91 patients (52 men and 39 women). Ninety-seven percent of the samples were analyzed with a unique assay technique in a unique laboratory. Five patients had a genetic variant (4 men and one woman). After discussion in the DVC, one male patient was considered to have a confirmed Fabry disease. He presented early signs of the disease (first-degree family history of cardiac or unexplained death, hypohidrosis, heat intolerance, tendency to chronic diarrhea, angiokeratoma, hypoacousia and tinnitus) which could have been identified earlier. The GLA variant was c.1185dupG / p.Phe396Glyfs, a clearly pathogenic frameshift variant. The prevalence of FD in included patients with biological data was 0.035% [0.006; 0.201] (0.058% [0.010; 0.33] in men, 0.000 % [0, 000; 0.350] in women). If we consider that patients who were not included because of a specific renal diagnosis unrelated to FD did not have FD, the estimated prevalence decreased to 0.028% [0.006; 0.121]. Conclusion: The estimated prevalence of FD in a cohort of French dialysis patients is 0.035% [0.006; 0.201], and by sex 0.058% in men [0.010; 0.328] and 0, 000% in women [0, 000; 0.35]. Although it appears extremely low, it remains justified to bring up this diagnosis in the event of an evocative sign, whether for the patient or his relatives as FD benefit of effective specific treatments. Funding for this Investigator Sponsored Study was provided by Sanofi Genzyme